1990
DOI: 10.1111/j.1600-0609.1990.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in idiopathic myelofibrosis: A simple scoring system with prognostic significance

Abstract: In a prognostic univariate analysis of a series of 80 patients with idiopathic myelofibrosis the Hb‐concentration, the platelet count and osteomyelosclerosis emerged as factors with prognostic significance. A Hb‐concentration < 10 g/dl was associated with a significantly shorter survival than a Hb‐concentration ≥ 10 g/dl. A platelet count < 100 × 109/1 also implied a significantly shorter survival. Patients with osteomyelosclerosis on X‐ray of the skeleton had a significantly better prognosis as compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The other aim of the treatment with ruxolitinib is the improvement of symptoms and the quality of life. The decrease in the MPN SAF score shows that there was an improvement in the symptoms for patients treated with ruxolitinib [30]. We also observes a reduction in transfusion dependence during the course of treatment.…”
Section: Discussionsupporting
confidence: 64%
“…The other aim of the treatment with ruxolitinib is the improvement of symptoms and the quality of life. The decrease in the MPN SAF score shows that there was an improvement in the symptoms for patients treated with ruxolitinib [30]. We also observes a reduction in transfusion dependence during the course of treatment.…”
Section: Discussionsupporting
confidence: 64%
“…In PMF, several studies have demonstrated the adverse prognostic relevance of advanced age,15, 16, 20, 22–25, 28 male sex,15, 22 anemia that is usually defined by a hemoglobin level of <10 g/dL,15–29 leukocytosis and/or leukopenia that is usually defined by a leukocyte count of <4 or >30 × 10 9 /L,15, 18–21, 25 thrombocytopenia that is usually defined by a platelet count of <100 × 10 9 /L,18–20, 25, 27 absolute monocyte count defined by a value of ≥1 × 10 9 /L,19 circulating blast percentage often defined as either ≥1% or ≥3%,15–17, 22 circulating immature granulocyte percentage of ≥10%,21 constitutional symptoms,16, 17 and cytogenetic abnormalities either in the bone marrow18–20, 32, 33 or splenic tissue 34. With regard to the relation between cytogenetic findings and survival, the presence of solitary abnormalities involving either 13q‐ or 20q‐ were associated with significantly better prognosis compared with all other abnormalities 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, recent information on disease pathogenesis has rejuvenated the focus on experimental targeted therapy as an alternative treatment strategy. In order to facilitate treatment decisions in PMF, a number of prognostic scoring systems (PSSs) have been constructed, based on the presence or absence of independent risk factors for survival 15–29. In the current, single institution‐based retrospective study of 334 patients with PMF (ie, meeting the WHO criteria for CIMF), we compared the performance of the most widely used PSS (the Dupriez PSS)15 against 2 other recently published models (the Cervantes PSS and the Mayo PSS)17, 19 that were derived from prognostic factors in younger patients (Table 1).…”
Section: Frequently Utilized Prognostic Models In Primary Myelofibrosismentioning
confidence: 99%
“…Material and methods 36 patients with IMF were studied. Most patients were included in clinical and collagen metabolic studies previously described (28)(29)(30)(31)(32)(33). Idiopathic myelofibrosis was defined by unexplained excessive accumulation of connective tissue in the bone marrow.…”
Section: -27)mentioning
confidence: 99%